Direct and ultrasensitive fluorescence detection of PETN vapor based on a fuorene-dimer probe via a synergic backbone and side-chain tuning. Issue 22 (22nd May 2018) - Liu, Ao; Liu, Huan; Peng, Xin; Jia, Jinlan; Fu, Yanyan; He, Qingguo; Cao, Huimin; Cheng, Jiangong
Abstract : Due to TPA attraction, the distance between PETN and 6TPA-2FT is shortened, and both PET and intermolecular forces are promoted. Abstract : Pentaerythritol tetranitrate (PETN), a major component in plastic explosives, poses a major threat to public safety and has extremely low saturated vapor pressure (7.17 ppt) and can hardly be detected directly. Two novel fluorescent sensing materials (6TPA-2FT and 6Py-2FT) were synthesized via Suzuki and Click reactions for a direct detection of PETN explosive vapor. The high binding affinity between the nitro group of PETN and the sensing film of 6TPA-2FT results in rapid and dramatic quenching of its fluorescence. The detection limit of 6TPA-2FT was as low as 0.056 ppt. The sensing mechanism was verified by various experimental characterization, including photophysical properties, SEM, IR, and quantum chemical calculations. For practical application, the sensing film of 6TPA-2FT was successfully used to detect PETN hidden in a bag using only naked eye detection under UV excitation without using any other complicated instrument, indicating its potential application for the detection of PETN vapors.